Nomadland eaudiobook Surviving america in the twenty-first century. - Bruder, Jessica (HighBridge Audio, 2017)
From the beet fields of North Dakota to the wilderness campgrounds of California to an Amazon warehouse in Texas, people who once might have kicked back to enjoy their sunset years are hard at work. Underwater on mortgages or finding that Social Security comes up short, they're hitting the road in astonishing numbers, forming a new community of nomads: RV and van-dwelling migrant laborers, or "workampers." Building on her groundbreaking Harper's cover story, "The End of Retirement," which brought attention to these formerly settled members of the middle class, Jessica Bruder follows one such RVer, Linda, between physically taxing seasonal jobs and reunions of her new van-dweller family, or "vanily." Bruder tells a compelling, eye-opening tale of both the economy's dark underbelly and the extraordinary resilience, creativity, and hope of these hardworking, quintessential Americans?many of them single women?who have traded rootedness for the dream of a better life.